PENGEMBANGAN MEDIA POP-UP BOOK DIGITAL BARTER FABEL UNTUK MENUNJANG LITERASI MEMBACA SISWA KELAS IV SD - Salsabila, Annisa; Dian Purnama Putri, Ragil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low reading literacy of students resulting from the suboptimal use of digital media in instruction. Consequently, the